ANALYZING THE IMPACTS OF INCREASE IN FOOD PRICES ON THE HOUSEHOLDS IN UNITED ARAB EMIRATES - Muhammad, S; Gheblawi, M. S.; Al-Neyadi, S. A. (Emirates Journal of Food and Agriculture, 2017)
According to recent statistics, the prices have increased about 14% in the United Arab Emirates (UAE). This increase in prices has affected the UAE diverse population differently. The main objective of this study was to analyze the perception of UAE household and to assess the economic and social impacts of increases in prices. The results showed that about half of the respondents do not have enough income to meet their daily needs. Majority of the respondents were affected severely with the recent increase in prices. The increase was much higher for rent, food, education and healthcare. Ordered Probit regression model was used to determine the factors affecting severity of increase in prices. The regression results showed that the effect of high prices varied among groups based on their age, ethnicity, gender, educational level and income. The paper provides useful information to policy makers in order to understand the impacts and design programs to deal with increase in prices.